The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1590/1518-8345.1398.2811
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the healing of complex surgical wounds in the breast and abdomen: retrospective cohort study

Abstract: Objective: to estimate the healing rate of complex surgical wounds and its associated factors. Method: retrospective cohort study from 2003 to 2014 with 160 outpatients of a Brazilian university hospital. Data were obtained through consultation of the medical records. Survival function was estimated using the Kaplan-Meier method and Cox regression model to estimate the likelihood of the occurrence of healing. Results: the complex surgical wound healing rate was 67.8% (95% CI: 60.8-74.9). Factors associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 20 publications
1
9
0
1
Order By: Relevance
“…The variables related to the surgical wound consisted of topography (abdomen, breast) and type of surgical intervention. The variables chosen were treated in a previous study on complex surgical wounds, directed by the authors of this study 2 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The variables related to the surgical wound consisted of topography (abdomen, breast) and type of surgical intervention. The variables chosen were treated in a previous study on complex surgical wounds, directed by the authors of this study 2 …”
Section: Methodsmentioning
confidence: 99%
“…And finally, third intention healing happens when the surgical wound is left open for a short period of time and the re-approximation of the edges is performed later 1 . Wound healing for first intention, called surgical site, can become complex (complex surgical wound) when the suture opens as the result of local complications such as seroma, hematoma, infection and dehiscence, requiring a longer time for spontaneous closure 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The main groups of chronic wounds of non-surgical origin are vascular ulcers of the lower limbs, neuropathic ulcers, such as those found in diabetics and pressure injuries (3,5,7) . Surgical wounds can be considered acute when healing happens by first intention and can become complex and chronic when they present complications such as dehiscence and infection, requiring healing by second intention (4,7) .…”
Section: Introductionmentioning
confidence: 99%
“…About 234 million surgeries are performed worldwide each year. A retrospective study based on data from the US Wound Registry, indicated that 20.8% of all types of wounds are represented by surgical wounds that did not heal, with an average cost of treatment for wound healing of US$ 3,927 (7) . This is an example of how the cost of treating surgical wounds with scar deficits can increase, due to the complexity and longer time of outpatient follow-up (7) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation